A quantitative, high-throughput urease activity assay for comparison and rapid screening of ureolytic bacteria - Cui, Ming-Juan (2022)
Urease is a dinickel enzyme commonly found in numerous organisms that catalyses the hydrolysis of urea into ammonia and carbon dioxide. The microbially induced carbonate precipitation (MICP) process mediated by urease-producing bacteria (UPB) can be used for many applications including, environmental bioremediation, soil improvement, healing of cracks in concrete, and sealing of rock joints. Despite the importance of urease and UPB in various applications, a quantitative, high-throughput assay for the comparison of urease activity in UPB and rapid screening of UPB from diverse environments is lacking. Herein, we reported a quantitative, 96-well plate assay for urease activity based on the Christensen's urea agar test. Using this assay, we compared urease activity of six bacterial strains (E. coli BL21, P. putida KT2440, P. aeruginosa PAO1, S. oneidensis MR-1, S. pasteurii DSM 33, and B. megaterium DSM 319) and showed that S. pasteurii DSM 33 exhibited the highest urease activity. We then applied this assay to quantify the inhibitory effect of calcium on urease activity of S. pasteurii DSM 33. No significant inhibition was observed in the presence of calcium at concentrations below 10 mM, while the urease activity decreased rapidly at higher concentrations. At a concentration higher than 200 mM, calcium completely inhibited urease activity under the tested conditions. We further applied this assay to screen for highly active UPB from a wastewater enrichment and identified a strain of S. pasteurii exhibiting a substantially higher urease activity than DSM 33. Taken together, we established a 96-well plate-based quantitative, high-throughput urease activity assay that can be used for comparison and rapid screening of UPB. As UPB and urease activity are of interest to environmental, civil, and medical researchers and practitioners, we envisage wide applications of the assay reported in this study.